Clinical and Hematological Profile of Patients Presenting with Extensively Drug-Resistant Enteric Fever - Ayaz, Muhammad; Khan, Inayat Ullah; Khan, Nouman; Nabi, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Extensively drug-resistant enteric fever has emerged as a major health concern among pediatric populations in endemic regions. Characterized by resistance to multiple first-line and second-line antibiotics, its clinical and hematological profile requires thorough evaluation to improve diagnostic and therapeutic strategies. Objective: To determine the frequency of clinical and hematological profiles of patients presenting with extensively drug-resistant enteric fever. Study Design: Descriptive cross-sectional study. Duration and Place of Study: This study was conducted from March 2024 to September 2024 at the Department of Pediatrics, Lady Reading Hospital, Peshawar. Methodology: A total of 113 children aged 1–15 years with blood culture-confirmed Salmonella Typhi resistant to five key antibiotic classes were enrolled. Patients underwent detailed clinical assessment and hematological evaluation using standard definitions for fever, coated tongue, hepatomegaly, splenomegaly, vomiting, abdominal pain, and diarrhea. Hematological parameters were assessed via EDTA blood samples using semi-automated analyzers. Results: The mean age of participants was 8.54 ± 4.31 years, with a mean weight of 22.02 ± 6.50 kg and average fever duration of 8.82 ± 2.85 days. Males constituted 65.5% of the sample. Clinically, 49.6% had a coated tongue, 39.8% had hepatomegaly, 29.2% experienced vomiting, 24.8% reported abdominal pain, 19.5% had diarrhea, and 17.7% showed splenomegaly. Anemia was found in 69.9%, thrombocytopenia in 39.8%, and leucopenia in 9.7% of patients. Conclusion: XDR enteric fever in children presents with a uniform clinical and hematological profile. Anemia and thrombocytopenia are prominent features.